Integrated Ophthalmic Trauma Units: Adopting an Orphan Discipline in Ophthalmology - Gangadhara Sundar, Rupesh Agrawal, Sundaram Natarajan (Pakistan Journal of Ophthalmology, 2016)
Ocular and ophthalmic trauma has increased tremendously in this world of modernization due to road traffic accidents and many other day to day mishaps. The World Health Organisation (WHO) had reported an annual occurrence of approximately 55 million eye injuries with incapacitation for more than one day. There are more than 1.6 million blind people secondary to ocular trauma with an additional 2.3 million having bilateral visual morbidity. 19 million people experience unilateral blindness or low vision from preventable injury1. Moreover, there is a global annual incidence rate of 3.5 open globe injuries per 100,000 persons, resulting in approximately 203,000 open globe injuries annually worldwide2.